Using Translation Activity to Improve the Students’ Vocabulary Mastery of the Eleventh Grade of Social Class at SMAN 3 Bojonegoro - Iin Widya Lestari; Adi Isma (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
Teaching English is very challenging nowadays. Senior high school students urgently are needed to be communicative in using English well. They need to be able to develop their English skills well. Dealing with mastering English skills, vocabulary is one of the crucial language components in learning English. In fact, most of the students faced difficulty in acquiring and mastering English vocabulary to support and develop their English skills. English teachers need to apply the appropriate strategy and activity to improve students’ vocabulary. This research aimed to know the process of improving students’ vocabulary mastery by using translation activity for Senior High school students at SMAN 3 Bojonegoro. This research used classroom action research. The subject of this research was students of Social Program at 11 B. In collecting the data, the writers used test items and observation sheets. The test was given pre-test, test 1 and test 2. Then the writers analyzed the mean score of each test to find out the improvement of students’ vocabulary mastery after the action was done. The result shows that there is an improvement in students’ vocabulary mastery. It could be seen from the score of the pretest is 42, posttest 1 is 47,8 and posttest 2 is 61. After conducting action research, it shows that students made good improvements in learning vocabulary. Based on the result of the research, it can be concluded that using translation activity can improve students’ vocabulary mastery.